2021
DOI: 10.3390/app11041753
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Subsoil CO2 Gas Measurements and Micrometeorological Monitoring: Above Canopy Turbulence Effects on the Subsoil CO2 Dynamics in Temperate Deciduous Forest

Abstract: Accurate and continuous measurement of the subsoil CO2 is critical to better understand the terrestrial and atmosphere gas transfer process. This work aims to develop and field test a specific flow system to continuously measure the soil gas concentration (χc) and understand its main physical drivers. Hourly data measured in situ were collected through two dedicated wells at 1 m and 6 m depth coupled with micrometeorological measurement. Our study shows that χc at -1 m was at the lowest in winter and highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Other studies have shown wind speed effects on soil gas transport (Adisaputro et al, 2021;Reicosky et al, 2008;Takle et al, 2004) or gas transport in snow (Bowling & Massman, 2011;Fujiyoshi et al, 2010). However, in most of these studies, the forcing pressure gradients have not been measured directly, and it cannot be differentiated between the effect of static pressure fields generated by the wind, mixing of the surface air, ventilating the ground vegetation or litter layer and windinduced pressure pumping, since all these phenomena correlate with wind speed.…”
Section: Static Pressure Fieldsmentioning
confidence: 99%
“…Other studies have shown wind speed effects on soil gas transport (Adisaputro et al, 2021;Reicosky et al, 2008;Takle et al, 2004) or gas transport in snow (Bowling & Massman, 2011;Fujiyoshi et al, 2010). However, in most of these studies, the forcing pressure gradients have not been measured directly, and it cannot be differentiated between the effect of static pressure fields generated by the wind, mixing of the surface air, ventilating the ground vegetation or litter layer and windinduced pressure pumping, since all these phenomena correlate with wind speed.…”
Section: Static Pressure Fieldsmentioning
confidence: 99%
“…The calibration data of the FTIR apparatus used herein (including the spectrometer and the gas cell) for the quantification of CO2 concentration over a range from 100 to 60 000 ppm was established in a previous work [22] (Fig. 4).…”
Section: Ftir Spectrometer Calibrationmentioning
confidence: 99%
“…For instance, the spectra of the combination band of CO2 (centered at 3610 cm -1 ) are strongly affected by the H2O vapor contribution at some concentration ranges and required a specific additional processing [16]. Also, the homonuclear diatomic gases (such as N2, O2) cannot be detected by FTIR spectroscopy whereas they are an important indicator about the biological activity of the soil (e.g., soil respiration processes) and the oxygenation conditions [19,17,[20][21][22]. On the other hand, the Raman technique can detect the most common natural gases (including CO2, CH4 as well as H2, O2 and N2…) but with lower sensitivity compared to that of FTIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to quantify the CO 2 absolute concentration from a previous mathematical calibration (polynomial type) of the band area data 55 extended by Adisaputro et al (2021) 82 for CO 2 measurements acquired with a resolution of 1 cm À1 . It provides an absolute concentration of CO 2 in ppmv.…”
Section: Continuous Gas Measurements By Raman and Infrared Spectroscopies In A Pz2 Ter Wellmentioning
confidence: 99%